(3eQGYGJ GdJhLg GddHfGfj ddefGgL GdLOjOI aj cJGH (B"(3HfGA GdQjGVjGJ(B" (3ddUa GdSGHY GdCSGSjs - (3YjJGfj, HdGds ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3cdjI GdJQHjI, GdYeGOIs, 2002)
(3JfGhdJ GdOQGSI eSCdI JhGab cJGH (B" (3HfGA GdQjGVjGJ (B" (3ddUa GdSGHY GdCSGSj GdUGOQ Yf GdeQcR GdJQHhj ddHMhK hGdEfeGA YGe (B1998 (3eY GdJhLg GdHfGFj ddefGgL GdLOjOI(B. (3hSYJ Edi eYQaI eOi JhGaQ HYV GdNUGFU GdHfGFjI aj GdCfTWI GdJMVjQjI OGNd GdcJGH(B. (3JeJ OQGSI aQhY GdCfTWI GdJMVjQjI aj cJGH (B" (3HfGA GdQjGVjGJ (B" (3hYOOgG (B122 (3aQYkG OGNd (B48 (3fTGWkG JXgQ HTcd CSFdI Ch WdHGJ Ch ehGba(B. (3hGYJeOJ GdOQGSI CQHYI eYGjjQ eMOOI eSJbGI ef efGgL GdQjGVjGJ GdLOjOI(B. (3Ke MOOJ dhGFM eDTQGJ eSJbGI ef GdCYeGd GdSGHbI aj eLGd GdCOHjGJ GdJQHhjI dJYdje GdQjGVjGJ hef JhLgGJ GdefGgL GdLOjOI ddGSJOdGd Ydi JhGaQ gPg GdeYGjjQ aj GdCfTWI(B. (3HGdEVGaI Edi EYJeGO eLehYI eDTQGJ dcd eYjGQ HYO eQGLYI GdeYGfj GdJj MGRJgG gPg GdeYGjjQ aj GdCOHjGJ GdJQHhjI(B. (3CXgQJ GdOQGSI Cf GdCfTWI GdJMVjQjI dG JJVef hVYjGJ CHOkG EfeG JJVef eSGFd, CeG eG JHbi efgG agj JeGQjf Ch WdHGJ dJfajP ELQGAGJ ZjQ eTcdjI Ch CfTWI ZjQ eUfaI(B. (3cPdc JHjf Cf LejY aQhY GdCfTWI eJhGabI eY LejY GdeYGjjQ GdeWQhMI, hCf GdCfTWI GdJMVjQjI JJjM EecGfjI UjGZI GdaQVjGJ aj LRA cHjQ efgG hdcfgG aj GdebGHd dG JJjM eYGdLI eSGFd eQJHWI HGdhGbY hdG WQM GdeSGFd hdG GdJObjb HaQVjGJ HTcd cGa(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Curriculum; Cycle moyen L$1 (Benseignement du Mathss; Intermediate Education Math education Curricula; (3GdeQMdI GdeJhSWI JYdje GdQjGVjGJ GdefGgLs